Early coronary angioplasty fails to lower all‐cause mortality in patients with out‐of‐hospital cardiac arrest without ST‐segment elevation: A systematic review and meta‐analysis - Khalid Rashid (10199826) (2024)
Introduction Out‐of‐hospital cardiac arrest (OHCA) is defined as the loss of functional mechanical activity of the heart in association with an absence of systemic circulation, occurring outside of a hospital. Immediate coronary angiography (CAG) with percutaneous coronary intervention is recommended for OHCA with ST‐elevation. We aimed to evaluate the effect of early CAG on mortality and neurological outcomes in OHCA patients without ST‐elevation. Methods This meta‐analysis and systemic review was conducted as per principles of Preferred Reporting Items for Systematic Reviews and Meta‐analysis (PRISMA) group. A protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO, Ref No. = CRD42022327833). A total of 674 studies were retrieved after scanning several databases (PubMed Central, EMBASE, Medline, and Cochrane Central Register of Controlled Trials). Results A total of 18 studies were selected for the final analysis, including 6 randomized control trials and 12 observational studies. Statistically, there was no significant difference in primary outcome, i.e., mortality, between early and delayed CAG. In terms of the grade of neurological recovery as a secondary outcome, early and delayed CAG groups also showed no statistically significant difference. Conclusion Early CAG has no survival benefits in patients with no ST elevations on ECG after OHCA. Other Information Published in: Health Science Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/hsr2.1379